The Optimization of Building Energy Consumption in Universitas Negeri Padang Using Building Energy Simulation Program - Kurniawan, Andre; Qosim, Nanang; Lapisa, Remon; Abadi, Zainal; Jasman, Jasman (Universitas Negeri Padang, 2021)
Energy consumption of a building is one of the biggest sources of energy use today. Green Building Comitte Indonesia (GBCI) has launched a concept of energy consumption saving in a nationally standard building. Audit Building energy audit is the way to know how actual building energy consumption is and find alternative solution to decrease energy consumption in order to fulfill the energy saving building criteria. Two types of HVAC systems will be run in the EnergyPlus simulation, split AC and central AC. The previous research proved that central AC is better than split AC system for energy saving in the building with 20 floors. The simulation results show that by using a certain energy system, a more efficient energy system will be achieved and can still maintain the comfort of the room at a temperature of 24 °C and relative humidity according to the Green Building Indonesia standard reference.